Payday holiday: How households fare after payday credit bans - Donald P. Morgan; Michael R. Strain (Federal Reserve Bank of New York, 2007)
Payday loans are widely condemned as a “predatory debt trap.” We test that claim by researching how households in Georgia and North Carolina have fared since those states banned payday loans in May 2004 and December 2005. Compared with households in states where payday lending is permitted, households in Georgia have bounced more checks, complained more to the Federal Trade Commission about lenders and debt collectors, and filed for Chapter 7 bankruptcy protection at a higher rate. North Carolina households have fared about the same. This negative correlation—reduced payday credit supply, increased credit problems—contradicts the debt trap critique of payday lending, but is consistent with the hypothesis that payday credit is preferable to substitutes such as the bounced-check “protection” sold by credit unions and banks or loans from pawnshops.
Keywords: G21; G28; I38; 330; payday credit; consumer welfare; bounced check protection; informal bankruptcy; Verbraucherkredit; Private Verschuldung; Georgia (Staat); North Carolina